Management of Village Fund Allocation (Add) in Realizing Good Governance in Baruta Lestari Village, Sangia Wambulu District - Sita, Nur; Husriah; Andriani Saputri (International Journal of Multidisciplinary Learners, 2025)
The aim of this research is to find out how Village Fund Allocation (ADD) is managed in realizing good governance in Baruta Lestari Village. The research method used is a qualitative descriptive method, with data collection techniques through in-depth interviews with village officials, direct observation of the fund management process, as well as documentation studies related to regulations and reports on ADD use. The research results show that the Management of Village Fund Allocation (ADD) in Baruta Lestari Village has implemented the principles of Good Governance, in the planning, implementation and accountability processes. The conclusion of this research is that in general, based on the results of research on the management of Village Fund Allocations (ADD) in realizing good governance in Baruta Lestari Village, the Management of Village Fund Allocations (ADD) in Baruta Lestari Village has been carried out in accordance with Permendagri No. 113 of 2014, includes planning, implementation and accountability involving the community. ADD management in Baruta Lestari Village is in accordance with the principles of Good Governance, especially in terms of transparency and accountability in reporting. However, there needs to be an increase in the aspect of community participation in monitoring village funds. The suggestion put forward is for the village government to carry out more outreach to the community regarding the importance of their role in supervision, as well as building a reporting mechanism that is more easily accessible to the community.